COLLECTION OF VARIOUS PARTICULATE MATTER USING AN ELECTROSTATIC PRECIPITATOR (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Over the past century, electrostatic precipitators (ESPs) have been widely applied in industry for the capture and separation of particulate matter due to their high collection efficiency and relatively low operational costs [1,2]. The current stage of ESP technology development — including its theoretical foundations, design structure, mathematical modeling approaches, electrical operating principles, power supply systems, gas conditioning techniques, hybrid precipitation technologies, and industrial applications — has been extensively covered in recent ESP conferences [3]. Furthermore, worldwide modernization efforts aimed at enhancing ESP performance have achieved important results in reducing particulate matter (PM) emissions and improving energy efficiency. Studies conducted at large-scale power plants in China [4] have demonstrated that nearly all ESP systems require upgrades to comply with PM2.5 (particulate matter with aerodynamic diameter below 2.5 μm) emission control targets. According to industrial field observations, a key reason for decreased ESP performance is insufficient particle charging at the inlet section, or a combination of such factors.